2007
DOI: 10.1161/01.res.0000266606.88463.cb
|View full text |Cite
|
Sign up to set email alerts
|

Increased Ventricular Preload Is Compensated by Myocyte Proliferation in Normal and Hypoplastic Fetal Chick Left Ventricle

Abstract: Abstract-Hemodynamics influence cardiac development, and alterations in blood flow may lead to impaired cardiac growth and malformations. The developing myocardium adapts to augmented workload by increasing cell number (hyperplasia). The aim of this study was to determine the influence of alterations in ventricular preload on fetal myocyte proliferation by manipulation of intracardiac shunting at the atrial level. We hypothesized that partial clipping of the right atrial appendage would increase the blood flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
87
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 35 publications
9
87
0
2
Order By: Relevance
“…Expressing the proliferative index in cells per volume of tissue results in less time-consuming cell counting and validation by counting in one group (ED6) also the total number of cell nuclei showed that the values were within the range of 15%-50% of positive myocytes, comparable with our previous studies in the embryonic chick (Sedmera et al, 2002a;deAlmeida et al, 2007). Apoptosis is a rare event in the developing ventricular myocardium and is considered a morphogenetic mechanism used for elimination of no longer needed subpopulations of myocytes in the AV region, outflow tract, and conduction system (Cheng et al, 2002;Sugishita et al, 2004).…”
Section: Abnormal Myocardial Developmentsupporting
confidence: 88%
“…Expressing the proliferative index in cells per volume of tissue results in less time-consuming cell counting and validation by counting in one group (ED6) also the total number of cell nuclei showed that the values were within the range of 15%-50% of positive myocytes, comparable with our previous studies in the embryonic chick (Sedmera et al, 2002a;deAlmeida et al, 2007). Apoptosis is a rare event in the developing ventricular myocardium and is considered a morphogenetic mechanism used for elimination of no longer needed subpopulations of myocytes in the AV region, outflow tract, and conduction system (Cheng et al, 2002;Sugishita et al, 2004).…”
Section: Abnormal Myocardial Developmentsupporting
confidence: 88%
“…Extensive studies using the chick embryo model have shown that epigenetic perturbations in blood flow can also lead to altered cardiovascular morphogenesis and congenital defects, implicating hemodynamics as a major environmental, epigenetic factor (deAlmeida et al 2007;Gessner 1966;Hogers et al 1999;Lucitti et al 2005;Reckova et al 2003;Sedmera et al 1999;Tobita et al 2005). This relationship has been validated for the global growth of the aortic arches by several studies, where changes in aortic arch perfusion by occlusion of a vitelline vein (Hogers et al 1999;Rychter and Lemez 1965), left atrial ligation (Hu et al 2009), manipulation of the outflow tract (Gessner 1966), or ligation of individual aortic arches (Rychter 1962) generated abnormal arch growth and defects in arch derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Shear stress modulates endothelial structure and function and results in an accurate regulation of endothelial gene expression in vitro (Dekker et al, 2002) and in vivo (Groenendijk et al, 2004;Dekker et al, 2005). Several animal models show that congenital malformations can result from disturbed blood flow (Hogers et al, 1997;Sedmera et al, 1999;Tobita et al, 2002;Hove et al, 2003;Dealmeida et al, 2007;Butcher et al, 2007). The large and rapid changes in volume and geometry of cardiac compartments during development are translated into local changes in shear stress and concomitant gene expression patterns of, e.g., Krü ppel like factor 2 (KLF2) (Groenendijk et al, 2004).…”
Section: Introductionmentioning
confidence: 99%